2012
DOI: 10.1158/1078-0432.ccr-12-0372
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Large Panel of Patient-Derived Tumor Xenografts Representing the Clinical Heterogeneity of Human Colorectal Cancer

Abstract: Purpose: Patient-derived xenograft models are considered to represent the heterogeneity of human cancers and advanced preclinical models. Our consortium joins efforts to extensively develop and characterize a new collection of patient-derived colorectal cancer (CRC) models.Experimental Design: From the 85 unsupervised surgical colorectal samples collection, 54 tumors were successfully xenografted in immunodeficient mice and rats, representing 35 primary tumors, 5 peritoneal carcinoses and 14 metastases. Histol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
326
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(365 citation statements)
references
References 24 publications
29
326
0
1
Order By: Relevance
“…KRAS mutations are well-established predictors of clinical resistance to anti-EGFR treatment in metastatic colorectal cancer ( 4 , 22 ), although this association is not strong in preclinical models (23)(24)(25). Our initial clinical development program focused on metastatic colorectal cancer with wild-type KRAS (determined on archived tumor samples), anticipating that Sym004 could overcome an acquired nongenetic mechanism of resistance to anti-EGFR treatment, even though we did see some activity of Sym004 in colorectal cancer cell lines with mutated KRAS in the presence of ligands.…”
Section: Research Articlementioning
confidence: 99%
“…KRAS mutations are well-established predictors of clinical resistance to anti-EGFR treatment in metastatic colorectal cancer ( 4 , 22 ), although this association is not strong in preclinical models (23)(24)(25). Our initial clinical development program focused on metastatic colorectal cancer with wild-type KRAS (determined on archived tumor samples), anticipating that Sym004 could overcome an acquired nongenetic mechanism of resistance to anti-EGFR treatment, even though we did see some activity of Sym004 in colorectal cancer cell lines with mutated KRAS in the presence of ligands.…”
Section: Research Articlementioning
confidence: 99%
“…Interestingly, these changes could not be reverted once the in vitro propagated cells were re-implanted into mice. Instead, PDTX retain the original tumor heterogeneity, thus allowing for clonal dynamic studies [6,25,30,[42][43][44][45][46]. Moreover, Eirew et al used deep genome and single cell sequencing methods to demonstrate an ongoing clonal selection in both primary and metastatic breast tumors, with the expansion of clones sharing recurrent patterns.…”
Section: Pdtx In Basic Cancer Research Modeling Tumor Heterogeneity Amentioning
confidence: 99%
“…First, patient-derived xenograft (PDX) tumor models are increasingly feasible and available. [26][27][28][29] Second, evidence is amassing that supports the cancer stem cell (CSC) paradigm: a theoretical model for cancer that accounts for the importance of specific tumor cell subpopulations to a tumor's growth and potential for driving tumor recurrence (reviewed in previous studies [30][31][32] ). Finally, next-generation DNA and RNA sequencing efforts (eg, The Cancer Genome Atlas) have demonstrated that very few common mutations unite particular solid tumor types; rather, patient tumors have a spectrum of mutations that collectively drive tumor growth.…”
Section: Addressing Tumor Heterogeneitymentioning
confidence: 99%
“…26,27,[55][56][57] As a natural extension of standard tissue culture techniques, some researchers have taken to the xenotransplantation of traditional tumor cell lines that have been passaged extensively in vitro. These models have empowered remarkable advances in the understanding of angiogenesis and tumor cell invasion, resulting in the development of therapeutic agents such as bevacizumab and sorafenib; 58,59 however, promising preclinical data obtained using these traditional cell line-initiated xenografts has not translated into dramatic improvements in overall survival in most cancer patients.…”
Section: Pdxs: Models For the 21st Centurymentioning
confidence: 99%